Green Synthesis and Characterization of Silver Nanoparticles Using Azadirachta indica Seeds Extract: In Vitro and In Vivo Evaluation of Anti-Diabetic Activity - Gauhar Rehman; Muhammad Umar; Nasrullah Shah; Muhammad Hamayun; Abid Ali; Waliullah Khan; Arif Khan; Sajjad Ahmad; Abdulwahed Fahad Alrefaei; Mikhlid H. Almutairi; Yong-Sun Moon; Sajid Ali (Pharmaceuticals, 2023)
Background: Diabetes mellitus (DM) is a non-communicable, life-threatening syndrome that is present all over the world. The use of eco-friendly, cost-effective, and green-synthesised nanoparticles as a medicinal therapy in the treatment of DM is an attractive option. Objective: In the present study, silver nanoparticles (AI-AgNPs) were biosynthesized through the green synthesis method using Azadirachta indica seed extract to evaluate their anti-diabetic potentials. Methods: These nanoparticles were characterized by using UV-visible spectroscopy, Fourier transform infrared spectrophotometers (FTIR), scanning electron microscopy (SEM), DLS, and X-ray diffraction (XRD). The biosynthesized AI-AgNPs and crude extracts of Azadirachta indica seeds were evaluated for anti-diabetic potentials using glucose adsorption assays, glucose uptake by yeast cells assays, and alpha-amylase inhibitory assays. Results: Al-AgNPs showed the highest activity (75 ± 1.528%), while crude extract showed (63 ± 2.5%) glucose uptake by yeast at 80 µg/mL. In the glucose adsorption assay, the highest activity of Al-AgNPs was 10.65 ± 1.58%, while crude extract showed 8.32 ± 0.258% at 30 mM, whereas in the alpha-amylase assay, Al-AgNPs exhibited the maximum activity of 73.85 ± 1.114% and crude extract 65.85 ± 2.101% at 100 µg/mL. The assay results of AI-AgNPs and crude showed substantial dose-dependent activities. Further, anti-diabetic potentials were also investigated in streptozotocin-induced diabetic mice. Mice were administered with AI-AgNPs (10 to 40 mg/kg b.w) for 30 days. Conclusions: The results showed a considerable drop in blood sugar levels, including pancreatic and liver cell regeneration, demonstrating that AI-AgNPs have strong anti-diabetic potential.